ANALISIS PRODUKTIVITAS DAN KONTRIBUSI PEMBUATAN ANYAMAN PURUN (Lepironia articulatta Domin) TERHADAP PENDAPATAN MASYARAKAT DI DESA PALAM KOTA BANJARBARU - Muhammad Suryani; Daniel Itta; Rina Muhayah Noor Pitri (Jurnal Sylva Scienteae, 2021)
This study aims to determine the amount of productivity and contribution to people's income from the purun woven handicraft industry in the form of mats and purun baskets in Palam Village, Banjarbaru City. This research was conducted in Palam Village, Cempaka District, Banjarbau City, South Kalimantan Province. The method used is the method of interviewing purun craftsmen at the research location by census. The data collection process is in the form of primary data and secondary data. net income. Productivity of mats per year of the people of Palam Village is Rp250,250,000.00 / year. Sari respondents with a net income of Rp26,947,500 / year while the lowest was obtained by Maisarah with a net income of Rp19,975,500 / year while the total net income of basket productivity per year of the people of Palam Village was Rp 241,170,000 / year. The highest annual productivity of mats was obtained by Susanti respondents with 256 pieces / year while the lowest was obtained by respondents from Anggi with 157 pieces / year. The highest productivity baskets per year were obtained by Susanti respondents with 2963 pieces / year while the lowest was obtained by Sari respondents with 1389 pieces / year. The highest annual contribution of the mats was obtained by respondents from Siti Romlah with a percentage of 75.35% per year, while the lowest was obtained by respondents from Susanti with a percentage of 67.05% per year with an average percentage of 71.55% per year. The highest average contribution of baskets per year was obtained by Siti Romlah respondents with a percentage of 74.76% per year while the lowest was obtained by respondents with a percentage of 64.83% with an average percentage of 70.82% per yearPenelitian ini bertujuan untuk mengetahui besarnya produktivitas dan kontribusi terhadap pendapatan masyarakat dari industri kerajinan anyaman purun berupa tikar, dan bakul purun di Desa Palam, Kota Banjarbaru. Penelitian ini dilaksanakan di Desa Palam, Kecamatan Cempaka, Kota Banjarbau, Provinsi Kalimantan Selatan. Metode yang dipergunakan adalah metode wawancara terhadap pengrajin purun di lokasi penelitian secara sensus. Pendapatan bersih Produktivitas tikar pertahun masyarakat Kelurahan Palam sebanyak Rp250.250.000,00 /tahun. Responden Sari dengan pendapatan bersih tertinggi sebesar Rp26.947.500/tahun sedangkan terendah diperoleh Maisarah sebesar Rp19.975.500 /tahun. Jumlah total pendapatan bersih Produktivitas bakul masyarakat Desa Palam sebanyak Rp241.170.000 /tahun. Produktivitas tikar pertahun terbanyak di peroleh responden Susanti dengan 256 buah/tahun sedangkan terendah diperoleh responden Anggi dengan 157 buah/tahun. Produktivitas bakul pertahun terbanyak di peroleh responden Susanti dengan 2963 buah/tahun sedangkan terendah diperoleh responden Sari dengan 1389 buah/tahun. Kontribusi tikar pertahun tertinggi di peroleh responden Siti Romlah dengan persentase 75,35% pertahun sedangkan terendah diperoleh responden Susanti dengan persentase 67,05% pertahun dengan rata-rata persentase 71,55% pertahun. Rata-rata kontribusi bakul pertahun terbanyak di peroleh responden Siti Romlah dengan persentase 74,76% pertahun sedangkan terendah diperoleh responden diah dengan pesentase 64,83% dengan rata-rata persentase 70,82% pertahun